1983
DOI: 10.1038/bjc.1983.30
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of lonidamine alone or combined with hyperthermia in some experimental cell and tumour systems

Abstract: Summary Lonidamine or 1-[(2, 4-dichlorophenyl) methyl]-lH-indazole-3-carboxylic acid, studied in a battery of in vitro and in vivo tests currently used for the screening of anti-tumour agents affecting cell division, has been shown to have a narrow spectrum of anti-tumour activity. The significance of this finding is discussed in the light of previous investigations suggesting that lonidamine affects mitochondrial function and not cell replication. Hyperthermia has been shown to sensitize tumour cells to lonid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…However, results of lonidamine phase II trials in breast cancer and other malignancies (Evans et al, 1984;Barduagni et al, 1984;Kokron et al, 1984) are of interest mainly because of the unique mode of action and toxicity of the drug, which suggest the potential for combination with radiotherapy (Hahn et al, 1984;Magno et al, 1984), hyperthermia (Silvestrini et al, 1983;Chitnis & Adwankar, 1986) and chemotherapy (Pacilio et al, 1984;Battelli et al, 1984). Until now, few controlled clinical trials of the combination of lonidamine with chemotherapy have been carried out in non-small cell lung cancer (Breau et al, 1988;Gallo Curcio et al, 1987), malignant glioma (Carapella et al, 1988) and bladder carcinoma (Giannotti et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, results of lonidamine phase II trials in breast cancer and other malignancies (Evans et al, 1984;Barduagni et al, 1984;Kokron et al, 1984) are of interest mainly because of the unique mode of action and toxicity of the drug, which suggest the potential for combination with radiotherapy (Hahn et al, 1984;Magno et al, 1984), hyperthermia (Silvestrini et al, 1983;Chitnis & Adwankar, 1986) and chemotherapy (Pacilio et al, 1984;Battelli et al, 1984). Until now, few controlled clinical trials of the combination of lonidamine with chemotherapy have been carried out in non-small cell lung cancer (Breau et al, 1988;Gallo Curcio et al, 1987), malignant glioma (Carapella et al, 1988) and bladder carcinoma (Giannotti et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…We wanted to exploit this natural preference of tumors for glycolytic metabolism as a method to selectively induce intracellular acidification of the tumor by accumulation of lactic acid even under aerobic conditions and use this selective tumor acidification and de-energization to enhance tumor response to chemotherapeutic agents, such as N-mustards and doxorubicin (11)(12)(13)(14)(15). Others had shown that LND sensitizes tumors to hyperthermia (23)(24)(25)(26), radiotherapy (27,28) and photodynamic therapy (29) by a variety of different mechanisms. In addition, to selectively acidifying and deenergizing human melanoma xenografts, LND had similar effects on mouse xenografts of triply-negative and triplypositive human breast cancer, human ovarian cancer and human prostate cancer (12), with the effect of LND increasing with the extent of glycolytic metabolism in the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Its cytotoxic activity observ ed in vitro on Ehrlich's ascites cells is parallel to the above-mentioned specific morphological changes of mitochondria and inhibition of both respiration and glycolysis [28,32], On the contrary, following Lonida mine administration to Ehrlich's ascites-bearing ani mals no antitumor activity is detected and tumor cell mitochondria appear normal; in the same experiment al conditions the combination of a mild hyperthermia with Lonidamine results in an inhibition of tumor growth which is accompanied by characteristic changes in tumor cell mitochondria [6]. Recent experi ments on isolated mitochondria have shown that both liver and Ehrlich's ascites mitochondria specifically bind Lonidamine when in stage 4 but not in stage 3 [33], These data are in agreement with the hypothesis that the susceptibility of tumor cells to Lonidamine depends on the stage of their mitochondria.…”
Section: Biochemical Datamentioning
confidence: 99%
“…Lonidamine is only active in sarcoma 180 and less regularly in Lewis lung carcinoma [4][5][6]. Lack of activ ity in P388 leukemia is worth mentioning since this tumor is used in some prescreening for antitumor activity [7].…”
Section: A Narrow Spectrum O F Antitumor Effectsmentioning
confidence: 99%